Growth and Survival of Kissing Gourami (Helostoma temminckii) in Maintenance Media from Liquid Biological Fertilizer - Aisyah, Siti; Rusliadi, Rusliadi; Pamukas, Niken Ayu (Jurnal Perikanan dan Kelautan, 2024)
This study aims to determine the growth and survival of kissing gourami (Helostoma temminckii) on a rearing medium given liquid biological fertilizer. This research was conducted from 01 April to 21 May 2022 at the Hatchery, Faculty of Fisheries and Marine, Universitas Riau. The container used was a bucket with a volume of 100 L. This study used a one-factor, Completely Randomized Design (CRD) method with five treatments and three replications. The level of treatment applied in this study was P0 = No treatment, P1 = treatment of 0.01 mL/L water, P2 = treatment of 0.03 mL/L water, P3 = treatment of 0.05 mL/L water and P4 = treatment of 0.07 mL/L. The results showed that applying liquid biological fertilizer with different doses significantly affected fish growth performance (P<0.05). The best treatment was found at a dose of 0.03 mL/L, which produced a range of ammonia (0.0043-0.0163 mg/L), nitrate (0.049-0.189 mg/L) phosphate (0.036-0.072 mg/L), absolute weight growth (10.07 g), absolute length growth (11.31 cm), specific growth rate (1.94%), feed conversion (1.08%) and survival (85, 00%).